2008
DOI: 10.1097/pcc.0b013e318166fa88
|View full text |Cite
|
Sign up to set email alerts
|

A neonate with coexisting congenital cystic adenomatoid malformation of the lung and alveolar capillary dysplasia: A case report with review of literature

Abstract: This is the first description of an association between these two rare malformations. Although a causative link between CCAM and ACD is possible, it is unlikely. ACD should always be considered as a cause of severe PPHN when persistent beyond 10 days, even if another etiology of PPHN is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Extrapulmonary findings are present in 50 to 80% of cases (10,14,21,25,30,33,34). Therefore, an infant with unexplained respiratory failure and structural abnormalities of the genitourinary, gastrointestinal, or cardiovascular systems should be evaluated for ACD/MPV (10,33).…”
Section: Physical and Laboratory Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrapulmonary findings are present in 50 to 80% of cases (10,14,21,25,30,33,34). Therefore, an infant with unexplained respiratory failure and structural abnormalities of the genitourinary, gastrointestinal, or cardiovascular systems should be evaluated for ACD/MPV (10,33).…”
Section: Physical and Laboratory Findingsmentioning
confidence: 99%
“…Therefore, an infant with unexplained respiratory failure and structural abnormalities of the genitourinary, gastrointestinal, or cardiovascular systems should be evaluated for ACD/MPV (10,33). Additionally, disruption of right-left asymmetry of the intrathoracic and/or intraabdominal organs has been reported in more than 25% of cases (10).…”
Section: Physical and Laboratory Findingsmentioning
confidence: 99%
“…Furthermore, many congenital lung masses regress in utero. Derderian et al directly compared fetuses with CDH and CPAMs and found that patients with CDH develop PH much more frequently than those with CPAMs (88% vs 18% respectively), suggesting that mass effect is not the sole driver of pulmonary artery hypoplasia in patients with CDH . The lower incidence of PH in fetuses with lung masses relative to those with CDH may be related to the later onset of disease and frequent regression during fetal life.…”
Section: Discussionmentioning
confidence: 99%
“…All ACD cases and 75% of the controls had TR velocities ≥ 3.2 m/sec ( of severe and fixed pulmonary hypertension attributed to "the deranged vascular endothelial growth factor signaling" have been previously described in ACD patients [14]. Furthermore, despite the presence of severe pulmonary hypertension and profound hypoxemia, neonates with ACD can be differentiated from others by relative initial sparing of lung parenchymal disease as exhibited by their relatively normal lung mechanics and compliance [1].…”
Section: Echocardiographicmentioning
confidence: 95%